Sella Turcica Anatomy by Three-Dimensional Computed Tomography for an Endonasal Transsphenoidal Approach to Pituitary Adenoma - Xiao, S.-X.; Ma, Y.-H.; Zhan, R.-Y.; Wen, L. (min - Minimally Invasive Neurosurgery, 2011)
The aim of this study was to identify the anatomic landmarks of sella turcica on the surface of the head, and to investigate the feasibility of studying sella turcica anatomy individually by three-dimensional computed tomography (3D-CT) before an endonasal transsphenoidal operation.The three-dimensional anatomic structures of the heads of 49 patients were studied by 3D-CT using image reconstruction with surgical clip image registration. The tip of the nose and the apex of the ear helix were used as surface markers on the head, and the locations of the sphenoid sinus and sellar floor with respect to a line defined by these 2 markers were investigated. Using an endonasal transsphenoidal approach with a surgical trajectory guided by the nose tip-ear apex line and 3D-CT anatomic images of the sella turcica, 12 patients with pituitary adenoma were treated surgically.The nose tip-ear apex line passed through the sphenoid sinus in 100% of the cases and through the sellar floor in 41.4% of the cases. The mean distance from the sellar floor clivus point perpendicularly to the nose tip-ear apex line was 3.5±2.0 mm. The 3D-CT imaging clearly showed the configuration of the sphenoid sinus, bone septum, optic protuberance, carotid protuberance and the sellar floor. 12 pituitary adenomas were resected totally.The nose tip-ear apex line provides a precise, simple, and practical tool for orienting the sphenoid sinus, sellar floor and surgical trajectory of the endonasal transsphenoidal approach. 3D-CT images more clearly and intuitively display the sella turcica anatomy. Preoperative 3D-CT increases the surgeon′s confidence in endonasal transsphenoidal operations and should be routinely performed in patients with pituitary adenomas.
Keywords: pituitary adenoma; 3D-CT; transphenoidal approach; image guidance; presurgical planning; endoscopy